The Role of Auditors in Assessing ESG-Based Tax Risks in Energy and Mining Companies - Antonius Juniarto; Isthi Wahyuning Tyas; Sarah Sarah; Handayani Sitohang (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study aims to explore how auditors assess tax risk in ESG-based mining companies and to identify the challenges faced in the tax audit process. The study also examines strategies that auditors can implement to ensure tax compliance, as well as their role in assisting companies in formulating tax policies that support sustainability. A qualitative case study approach to explore how auditors assess and manage tax risk in ESG-based mining companies using thematic analysis. The study focuses on an in-depth analysis of tax audit practices and sustainability regulations applied within the company. Indicated that many employees still lack a deep understanding of PSAK and the taxation system, particularly carbon-related taxation. This lack of understanding creates obstacles that reduce work effectiveness and results that do not meet expectations. Another finding shows that ESG reporting systems and implementation remain weak due to the absence of comprehensive application, indicating the need for socialization programs and seminars. This findings highlight the importance of a strong foundational understanding of PSAK, especially within the mineral and mining sectors, to ensure proper and accurate application. In addition, a deep understanding of taxation is essential. In the ESG context, several interview findings indicate that reporting is not yet sufficiently detailed due to a limited understanding of the importance of ESG. This study contributes to greater openness in the academic field by emphasizing the need for new and broader knowledge in accounting that supports sustainable company growth. Continuous growth enables companies to remain profitable and enhance firm value.